Geo-Aspect Analysis and Area Altitude Distribution of Glaciers in Doda Valley, Zanskar Basin, Jammu & Kashmir, India - Rai, Praveen Kumar; Nathawat, M. S.; Mohan, Kshitij (National Geographical Journal of India, 2022)
Not available